Damping of exciton Rabi rotations by acoustic phonons in optically excited InGaAs/GaAs quantum dots. - Ramsay, A; Gopal, A; Gauger, E; Nazir, A; Lovett, B; Fox, A; Skolnick, MS (2010)
We report experimental evidence identifying acoustic phonons as the principal source of the excitation-induced-dephasing (EID) responsible for the intensity damping of quantum dot excitonic Rabi rotations. The rate of EID is extracted from temperature dependent Rabi rotation measurements of the ground-state excitonic transition, and is found to be in close quantitative agreement with an acoustic-phonon model.